La creación de una red consular como base para el asentamiento de las relaciones internacionales - Manuel Talamante Pérez (Mélanges de la Casa de Velázquez)
The article shows the genesis and development of the consular institution in one of the young American republics: Uruguay. This is a significant and interesting case to confirm the running and formation of the consular network in one of the states that emerged after the emancipation period and the collapse of the Spanish Empire. Showing the origin of this institution will allow us to know the development and formation of an institution that will establish the international relations between Uruguay and the countries in which these consulates are installed in a period of change and in which the bases of the agricultural export model were beginning to expand. To this end, primary sources from the Ministry of Foreign Affairs of Uruguay and secondary sources dealing with this subject have been worked on.